الطرق الداخلية الموحدية ودورها في التبادل التجاري البحري خلال القرنين 6–7هـ/12–13م (Comprehensive Journal of Science, 2025)
This research paper examines and analyzes the contributions of inland routes to the development of maritime trade during the Almohad era, focusing on the vital role played by transportation networks and the natural environment in strengthening the economic connection between the Maghreb and al-Andalus. The network of overland routes—both coastal and inland—helped link cities and commercial centers through organized pathways that extended from Ceuta and Tangier in the north to Sijilmasa and Tripoli in the south, and from the western Maghreb to al-Andalus in the east and west. This system facilitated a smooth and continuous movement of merchants and goods toward the major ports.Likewise, Moroccan and Andalusian rivers—such as the Sebou, Shuqur, and Guadalquivir—served as effective navigational routes for transporting goods from the interior to the coast, where small boats and river vessels contributed to the efficient exchange of commodities between cities and ports. This represented an integrated economic system combining land, river, and maritime transport, which stimulated the growth of Moroccan exports—particularly agricultural and industrial products—and enabled the import of Mediterranean goods that enhanced the state’s position within the international trade network of the period.The study also highlights the importance of commercial caravans and transport methods, as well as the role of tribes in protecting routes and regulating traffic, in addition to the impact of trade-related taxation on supporting the state treasury and developing its economic infrastructure. Through the analysis of these elements, the paper concludes that the Almohad state succeeded in establishing an advanced and balanced economic system connecting the hinterland, the coast, and the sea. This system positioned the Almohads as a pivotal center of trade and cultural exchange between the Islamic and Christian worlds during the Middle Ages, reinforcing their status as a major economic power in the western Mediterranean.
Keywords: Almohads; (Maghrib and al-Andalus); land and river routes; means of transport; commercial centers; rivers; determining distances between cities; frontier zones.